(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article examines the scientific and theoretical foundations as well as the practical issues involved in teaching the literary and philosophical heritage of Abai Kunanbayuly. The literary, philosophical, pedagogical, and cultural dimensions of studying Abai’s works are systematized, and the theoretical principles underlying the teaching of the discipline are defined. In addition, the formation of Abai studies as an independent scholarly field and its place within the education system are analyzed. The authors substantiate innovative approaches to transmitting Abai Kunanbayuly’s rich heritage to the younger generation in accordance with contemporary demands, highlighting the specific features of its instruction in higher education and the continuity of teaching the poet’s legacy in secondary education. The causes of the existing gap in this continuity and its current consequences are demonstrated and supported with concrete examples. The article presents both established teaching methods and modern digital technologies for promoting the poet’s heritage. The current key directions in teaching Abai Kunanbayuly’s works are scientifically grounded, and their methodological foundations are clearly defined. In particular, special attention is given to various interpretations related to the stage-specific features of historicism in studying the poet’s legacy, as well as to the pedagogical aspects of teaching the scientific concept of Abai’s poetic school formulated by M. O. Auezov. Furthermore, the authors analyze scholarly and methodological studies devoted to teaching the poet’s works and provide contemporary interpretations of the most significant of them. The identification of the principal directions in teaching the theoretical foundations of Abai studies determines the relevance of this article.